1998
DOI: 10.4067/s0370-41061998000500004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrobroncoscopia en pediatría: utilidad diagnostica y terapéutica.

Abstract: Re sum enSe analizcn "• 37 fibrobro-xoscopias reahzadas en 121 pacientes duranre 25 meses (abril 1995 a mayo 19971 con rongo de edad entre 20 dias a 15 anos y p'omedic de A3 anos. Noventa y cinco proced'mientos Fueron diagn6s r icos (70%],. e resto terapeutico. Las principals rdicac'ones clinicos que en su conjun'c representan el 77% de los procedimienros fueron: atelec'asias (3'%)., lavado oroncoalveola r |22%), estridor [14%) y evaluacion de! paciente traqueostomizado cronicc 110%]. Veintidos de los procedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
1
0
6
Order By: Relevance
“…FB plays a complementary role to other diagnostic tools and/or radiological images. In our series, among nine different indications for FB, the three most frequentetiological study of atelectasis, stridor, and pneumoniacorrespond to the same as those reported in several general pediatric series, [2][3][4][5][6][7] reflecting that pulmonary disorders may not be necessarily related to a specific cardiac diseases. Many of them are related to underlying conditions or diseases of the child (e.g., pneumonia and immunosupression) and this was present in almost twothirds of our patients (61.1%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…FB plays a complementary role to other diagnostic tools and/or radiological images. In our series, among nine different indications for FB, the three most frequentetiological study of atelectasis, stridor, and pneumoniacorrespond to the same as those reported in several general pediatric series, [2][3][4][5][6][7] reflecting that pulmonary disorders may not be necessarily related to a specific cardiac diseases. Many of them are related to underlying conditions or diseases of the child (e.g., pneumonia and immunosupression) and this was present in almost twothirds of our patients (61.1%).…”
Section: Discussionsupporting
confidence: 78%
“…1 Over this period, several groups have reported their general experience with FB in children. [2][3][4][5][6] Fifteen years ago pediatric FB was introduced in Chile and during the last 13 years nearly 1,200 procedures have been performed at the Catholic University Hospital in Chile. We have previously reported our experiences with FB assessment in children.…”
Section: Introductionmentioning
confidence: 99%
“…En esta serie se realizaron procedimientos que consistieron en extracción de cuerpo extraño, cierre de fístulas broncopleurales, intubación difícil y resección de un granuloma subglóti-co con el apoyo de broncoscopia rígida. Se reportó un porcentaje de complicaciones menor al 1% 21 . Schellbase y cols, publicaron la utilidad clínica de la broncoscopia flexible y LBA en lactantes con sibilancias recurrentes 22 , con un porcentaje significativo de LBA positivo a cultivos virales, y a macrófagos cargados de lípidos, sugerentes de aspiración pulmonar.…”
Section: Discussionunclassified
“…El LBA fue realizado en cada uno de los hospitales por médicos especialistas en patología broncopulmonar, empleando fibrobroncoscopio pediátrico flexible y usando técnica estándar 4 . El fibrobroncoscopio fue localizado en las zonas de interés según la información imagenológica o en el lóbulo medio, instilándose por el canal de trabajo tres alícuotas de 1 ml/kg de solución salina fisiológica (NaCl 9‰) estéril.…”
Section: Pacientes Y Métodosunclassified
“…Debido a la gravedad potencial de estos pacientes el tratamiento antimicrobiano de amplio espectro es iniciado empíricamente siendo la demostración de la etiología de gran importancia para ajustar o suspender la terapia antimicrobiana 2 . Se ha demostrado que el LBA por fibro-broncoscopia (FBC) en niños es un procedimiento eficiente que permite confirmar la etiología de cuadros infecciosos pulmonares en forma rápida y confiable, con pocas complicaciones, las que de producirse son usualmente leves y sin mortalidad [3][4][5] . El procedimiento es efectivo y bien tolerado en pacientes oncológicos incluso en condiciones de insuficiencia respiratoria [6][7][8][9] .…”
unclassified